Case Report: Acquired Disseminated BCG in the Context of a Delayed Immune Reconstitution After Hematological Malignancy - Gies, Vincent; Dieudonné, Yannick; Morel, Florence; Sougakoff, Wladimir; Carapito, Raphaël; Martin, Aurélie; Weingertner, Noëlle; Jacquel, Léa; Hubele, Fabrice; Kuhnert, Cornelia; Jung, Sophie; Schramm, Frederic; et al. (Frontiers in Immunology, 2021)
Context: Disseminated infections due to Mycobacterium bovis bacillus Calmette-Guérin (BCG) are unusual and occur mostly in patients with inborn error of immunity (IEI) or acquired immunodeficiency. However, cases of secondary BCGosis due to intravesical BCG instillation have been described. Herein we present a case of severe BCGosis occurring in an unusual situation. Case description: We report one case of severe disseminated BCG disease occurring after hematological malignancy in a 48-years old man without BCG instillation and previously vaccinated in infancy with no complication. Laboratory investigations demonstrated that he was not affected by any known or candidate gene of IEI or intrinsic cellular defect involving IFNγ pathway. Whole genome sequencing of the BCG strain showed that it was most closely related to the M. bovis BCG Tice strain, suggesting an unexpected relationship between the secondary immunodeficiency of the patient, and the acquired BCG infection. Conclusion: This case highlights the fact that, in addition to the IEI, physicians, but also microbiologists and pharmacists should be aware of possible acquired disseminated BCG disease in secondary immunocompromised patients treated in centers that administrate BCG for bladder cancers.